Oxytocin Facilitation of Emotional Empathy Is Associated With Increased Eye Gaze Toward the Faces of Individuals in Emotional Contexts - Le, Jiao; Kou, Juan; Zhao, Weihua; Fu, Meina; Zhang, Yingying; Becker, Benjamin; Kendrick, Keith M. (Frontiers in Neuroscience, 2020)
One of the most robust effects of intranasal oxytocin treatment is its enhancement of emotional empathy responses across cultures to individuals displaying emotions in realistic contexts in the multifaceted empathy task (MET). However, it is not established if this effect of oxytocin on emotional empathy is due to altered visual attention towards different components of the stimulus pictures, or an enhanced empathic response. In the current randomized placebo controlled within-subject experiment on 40 healthy males, we both attempted a further replication of emotional empathy enhancement by intranasal oxytocin (24IU) and used eye-tracking measures to determine if this was associated by altered visual attention towards different components of the picture stimuli (background context, human face and body posture). Results replicated previous findings of enhanced emotional empathy in response to both negative and positive stimuli and that this was associated with an increased proportion of time viewing the faces of humans in the pictures and a corresponding decrease in that towards the rest of the body and/or background context. Overall, our findings suggest that enhanced emotional empathy following oxytocin administration is due to increased attention to the faces of others displaying emotions and away from other contextual and social cues.